2009
DOI: 10.1007/s12010-009-8866-7
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Green Algae Chlorella sp. in Different Wastewaters from Municipal Wastewater Treatment Plant

Abstract: The objective of this study was to evaluate the growth of green algae Chlorella sp. on wastewaters sampled from four different points of the treatment process flow of a local municipal wastewater treatment plant (MWTP) and how well the algal growth removed nitrogen, phosphorus, chemical oxygen demand (COD), and metal ions from the wastewaters. The four wastewaters were wastewater before primary settling (#1 wastewater), wastewater after primary settling (#2 wastewater), wastewater after activated sludge tank (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
358
5
24

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 918 publications
(436 citation statements)
references
References 30 publications
25
358
5
24
Order By: Relevance
“…These culture flasks were incubated on a shaker (150 rpm) under ambient conditions of (20 ± 3°C) temperature and natural sunlight at alternating light-dark photoperiod (14 h:10 h) for 20-30 days (Wang et al 2010). Furthermore subculturing was performed by inoculating 50 ll of algae cultures onto test tubes containing solidified BBM slants with 1.5% (w/v) of agar powder.…”
Section: Inoculum Preparation and Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…These culture flasks were incubated on a shaker (150 rpm) under ambient conditions of (20 ± 3°C) temperature and natural sunlight at alternating light-dark photoperiod (14 h:10 h) for 20-30 days (Wang et al 2010). Furthermore subculturing was performed by inoculating 50 ll of algae cultures onto test tubes containing solidified BBM slants with 1.5% (w/v) of agar powder.…”
Section: Inoculum Preparation and Maintenancementioning
confidence: 99%
“…6). According to Wang et al (2010), the relative constancy of nitrate uptake by algae might be due to the saturation of assimilators to amino grouping production for entry into nitrogenous metabolism. This homeostasis of nitrogen assimilation enables it to maximize growth, which supports our findings.…”
Section: Analysis Of Treated Wastewater Samplementioning
confidence: 99%
“…Chlorella sp. removed 24.8 % of COD in 9 days from secondary treated municipal wastewater filtered through 0.2-lm membrane (Cho et al 2011). Wang et al (2010b revealed that Chlorella sp.…”
Section: Heavy Metal Removal By Microalgae In Wastewatermentioning
confidence: 99%
“…Microalgae are emerging as most sustainable candidate for biofuel production. Some advantages such as easily cultivable, usage of non-arable land, no competition with food crops for land and water, nutrients uptake from wastewater, ability to produce substantial amount of triacylglycerides (TAG) and shorter doubling time make them better than other available feedstocks (Kiran et al 2014a;Sharma et al 2012;Wang et al 2009). …”
Section: Introductionmentioning
confidence: 99%